Pt-tnts for conversion of carbon dioxide to methane - Azrina, Abd Aziz; Nor Afifah, Abdullah; Sandran, Nivaashini (2021)
To synthesize TNTs and Pt-TNTs for conversion of CO2 to CH4 under visible light spectrum. To characterize the physical properties and optical properties of synthesized photocatalyst. To evaluate the photocatalytic efficiency between Pt-TNTs and TNTs through the degradation of carbon dioxide.